(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
His research was conducted with the aim of knowing the level of success of learning mathematics using the AJEL (Active, Joyful, Effective Learning) learning method. Previously, mathematics learning was still in the form of learning using the lecture method. The lecture method makes students less interesting with the learning that is done. Learning with the AJEL method (Active, Joyfull, Effective Learning) is expected to increase students’ interest in learning. The research method was carried out by means of class action assessments which were carried out at SD Negeri 1 Bandung located in Nganjuk Regency with class 5 research subjects with a total of 15 students. Data obtained by observation, as well as direct classroom action. From the results of the study, it was concluded that the use of the AJEL learning method in learning mathematics in grade 3 SD Negeri 1 Bandung can increase students’ interest in learning mathematics